2004
DOI: 10.1002/eji.200424856
|View full text |Cite
|
Sign up to set email alerts
|

Frontline: Optimal T cell activation requires the engagement of CD6 and CD166

Abstract: The T cell surface glycoprotein, CD6 binds CD166 in the first example of an interaction between a scavenger receptor cysteine-rich domain and an immunoglobulin-like domain. We report that in human these proteins interact with a K D =0.4-1.0 ? M and K off n 0.4-0.63 s -1 , typical of many leukocyte membrane protein interactions. CD166 also interacts in a homophilic manner but with around 100-fold lower affinity (K D =29-48 ? M and K off n 5.3 s -1 ). At concentrations, that will block the CD6/CD166 interaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
145
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 45 publications
(74 reference statements)
14
145
0
1
Order By: Relevance
“…In conclusion, we have identified syntenin-1 as the first intracellular partner reported for human CD6, a lymphocyte surface receptor involved in proper IS maturation (17) and T cell proliferation (17,18). The accumulation of syntenin-1 at the IS recalls that previously reported at the neural synapse and suggests that syntenin-1 (alone or in conjunction with other PDZ-containing proteins) may be relevant for processes that occur not only at the neural, but also the IS.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In conclusion, we have identified syntenin-1 as the first intracellular partner reported for human CD6, a lymphocyte surface receptor involved in proper IS maturation (17) and T cell proliferation (17,18). The accumulation of syntenin-1 at the IS recalls that previously reported at the neural synapse and suggests that syntenin-1 (alone or in conjunction with other PDZ-containing proteins) may be relevant for processes that occur not only at the neural, but also the IS.…”
Section: Discussionsupporting
confidence: 77%
“…This represents not only the first reported protein-protein interaction involving the intracytoplasmic region of CD6, but also the first description of the involvement of syntenin-1 in the protein-protein interactions taking place during IS maturation. CD6 is a lymphocyte surface receptor, which mediates cell-to-cell interactions relevant to IS maturation (17) and T cell proliferative responses (17,18). However, the intracellular interactions responsible for these CD6-mediated effects are mostly unknown to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,38,39 Itolizumab, an anti-CD6 mAb, has demonstrated clinical benefits, 33,40 as well as modulation of T cell proliferation and decrease of proinflammatory cytokine levels in psoriasis patients. 35 Studies have shown that itolizumab is not a T cell-depleting antibody when used as monotherapy both in Cuban RA 33 and psoriasis (unpublished data) patients.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The interaction between ALCAM and the CD6 molecule is one of the costimulatory pathways of T cell activation. 24,25 An anti-CD6 monoclonal antibody (mAb) that prevented renal and bone marrow graft rejection 26,27 was evaluated in multiple sclerosis patients, and a significant reduction in peripheral T cell counts was found. 28 More recently, the finding of CD6 as a susceptibility gene in multiple sclerosis, 29,30 as well as the overexpression of ALCAM and the presence of CD6+ T and B cells in salivary glands of patients with Sj€ ogren syndrome, 31 support the role of CD6 in pathological autoimmunity and reinforces its relevance for targeted therapy.…”
Section: Introductionmentioning
confidence: 99%